Parallelisms between Jungian Archetypes with Ibn ‘Arabi’s Concept of Ayani-Sabita - Turgay Şirin (Spiritual Psychology and Counseling)
This study attempts to put forth the relationship between Carl Gustav Jung’s concept of the archetype and Muhyiddin Ibn ‘Arabi’s concept of Ayani-sabita. In this context, the nature of the concepts of Muhyiddin Ibn ‘Arabi’s Ayani-sabita and Jung’s concept of the archetype are examined, as well as the similarities and differences between each of the two concepts, by researching the issues of the relationship of these concepts with existence and humans. Attention is attempted to be drawn in the study’s results to the topics that the concept of Ayani-sabita, which is often unrecognized in the literature on psychology, can contribute to contemporary psychology, arriving at the conclusion that this concept may be one that can contribute to the science of psychology just as Jung’s archetype concept.